Cryptocoryne aura (Araceae), a new species from West Kalimantan, Indonesia - Suwidji, Wongso; Isa, Ipor; Cheksum, Tawan; Hendra, Budianto; Bastmeijer, Jan D.; Jacobsen, N. (Botanischer Garten und Botanisches Museum Berlin-Dahlem, 2016)
A new species, Cryptocoryne aura Wongso & Ipor, from West Kalimantan, Indonesia, is described and illustrated. It differs from other Cryptocoryne species primarily by having a transparent, ciliate membrane along the leaf margin and a short spathe with a yellow, forward-twisted limb. It has a chromosome number of 2n = 26, which has not hitherto been recorded within the genus. The morphology of the germinating seed is unique within the genus, the embryo emerging c. ⅓ from the distal end of the seed with 3(or 4) plumulary processes (prophylls).